CONSTITUTIONAL CONUNDRUM: AGE ELIGIBILITY DILEMMAS AND THE DYNAMICS OF POLITICAL LEADERSHIP IN CONTEMPORARY INDONESIA - Shohib Muslim; Asri Agustiwi, Desi Syamsiah, Arga Baskara, Febri Atikawati Wiseno Putri (Adisam Publisher, 2024)
This exhaustive study thoroughly examines the constitutional intricacies surrounding age eligibility criteria for political leadership in contemporary Indonesia. Through an in-depth literature review and comprehensive analysis, this research probes the multifaceted dimensions of the Constitutional Court's decisions, particularly in high-profile cases involving figures such as Gibran Rakabuming Raka and Prabowo Subianto. The exploration extends beyond legal perspectives to encompass the challenges confronted by the court and the broader implications of these rulings on the landscape of political leadership. By unraveling the complex interplay between legal doctrines, societal expectations, and democratic principles, the study contributes significantly to a nuanced understanding of how age-related criteria intersect with leadership attributes and shape public perception. As Indonesia stands at the crossroads of tradition and modernity, grappling with these constitutional dilemmas, the outcomes not only carry substantial implications for the nation itself but also furnish invaluable insights into the evolving dynamics of democracy within the global context.